2016
DOI: 10.5713/ajas.16.0203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of yeast with bacteriocin and Lactobacillus culture on growth performance, cecal fermentation, microbiota composition, and blood characteristics in broiler chickens

Abstract: ObjectiveThe aim of the present study was to investigate the effect of yeast with bacteriocin and Lactobacillus cultures (mixture of Lactobacillus agilis BCRC 10436 and Lactobacillus reuteri BCRC 17476) supplements, alone or in combination, on broiler chicken performance.MethodsA total of 300, 1-d-old healthy broiler chickens were randomly divided into five treatment groups: i) basal diet (control), ii) basal diet+0.25% yeast (Saccharomyces cerevisiae) (YC), iii) basal diet+0.25% yeast with bacteriocin (BA), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
1
38
0
2
Order By: Relevance
“…Nevertheless, the supplementation of the diets with yeast probiotics at 0.15 to 0.3% have been shown to improve the performance of birds to a level achieved by the use of dietary antibiotic levels (Onifade et al, 1999). It has been recently shown that this kind of effect is due to the bacteriocin-producing effects of yeast probiotics when used single or together with lactic acid bacteria species in the diet of broiler chickens (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the supplementation of the diets with yeast probiotics at 0.15 to 0.3% have been shown to improve the performance of birds to a level achieved by the use of dietary antibiotic levels (Onifade et al, 1999). It has been recently shown that this kind of effect is due to the bacteriocin-producing effects of yeast probiotics when used single or together with lactic acid bacteria species in the diet of broiler chickens (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which kefir affects poultry performance is largely unknown, where as, it is welles tablished that probiotics which contain Lactobacillus culture can control the pathogens population and alter gastrointestinal flora (Chen et al, 2016). These effects can increase the activity of intestinal enzymes and digestibility of nutrients (Dierck, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus culture into broiler feed result in an increase in feed conversion ratio (Yu et al, 2007;Chen et al, 2016). It is noteworthy that the different effects of probiotics, including relation of intestinal microflora (Yu et al, 2007;Chen et al, 2016) and immune system ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contradictory results on growth performance in broiler may be attributed to the fact that probiotics cannot show activity in the intestinal system of broilers. Because, Chen et al, (2017b) reported that dietary SC supplementation did not affect body weight gain, caecal lactic acid bacteria (LAB), Enterococcus, total anaerobic bacteria and short chain fatty acids. Also it was reported that dietary SC supplementation did not affect body weight gain and caecal LAB count of broilers although dietary SC supplementation increased villi length and total volatile fatty acids and decreased caecal E. Coli (Teng et al, 2017;Haldar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%